Enquadramento de corpos de água em pequenas e micro bacias hidrográficas rurais de base agrícola familiar: subsídios à elaboração da fase diagnóstica - Gallina, Karla Libardi (2014)
This work has the overall proposal provide grants for the development of the diagnostic phase of the framework of bodies of surface water from small and micro watersheds (PMBH). His justification sustains the fact that the implementation of processes framework is still limited, mainly regarding the PMBH, management scale not seen for managing water resources. Presented as objective the identification, analysis and selection of diagnostic criteria adopted in the framework processes; review as the particularities / specificity regarding the use of these diagnostic items for PMBH reality, and finally, to propose guidelines for the establishment of guidance procedures for diagnostic evaluations for purposes of framework of bodies of surface water in PMBH. Methodologically grounded through analysis of technical and scientific studies, diagnostic items identified were grouped in a systematic way, and conducted assessment as to the applicability of these items in preparation for diagnostic framework in PMBH. As a result, proved possible to obtain greater detail for the items of diagnoses suggested by Resolution No. 91/08 CNRH in Article 4. Presented as a product, a set of items of diagnostic reference to the stage of diagnostic evaluations of the Framework. Also showed that there was indeed particularities that should be taken into consideration for the development of studies in small river basin framework. Furthermore, with the proposal of guidelines for establishing a guideline for the diagnostic phase of the framework procedures, found that the challenges to make reality the framework of bodies of surface water in PMBH are financial and technical-scientific, political.